"Here's herself" : An Analysis of Nonstandard Hiberno-English Grammatical Features in Normal People: The Scripts - Hautaniemi, Venla (My University, 2026)
The role of sociolinguistics in dialectological studies is of increasing interest and importance in contemporary research. Due to its historical development and role, Hiberno-English as the primary variety in Ireland offers copious opportunities to inspect its features and their sociolinguistic implications. This thesis explores the nonstandard Hiberno-English grammatical features evident in Normal People: The Scripts and the social patterns in which they occur. Through close reading selected features are identified in the material and noted along with the speakers of those features. Standard English is utilised as a reference grammar to interpret the marked features. An analysis on the social factors of the speakers enables the search for social patterns in the language use. The results of this thesis include an overview of the frequency and nature of three nonstandard Hiberno-English grammatical features in the data as well as their association with two social factors. The strongest social pattern emerges between gender and the nonstandard features. The results of this study reveal that contemporary literature contains significant instances of dialectal vernacular and that certain social factors correlate with that language use. Simultaneously, the results also highlight the multilayered and complex nature of sociolinguistic research.
Keywords: dialectology; Hiberno-English; grammar; nonstandard; sociolinguistics; linguistic variable; social pattern